Marketingová strategie pro společnost Eurovia - Kvapil, Antonín (Vysoké učení technické v Brně. Fakulta podnikatelská, 2011)
Diplomová práce se zabývá návrhem a tvorbou marketingové strategie. Práce popisuje stav společnosti Eurovia CS, a.s., analyzuje mikroekonomické a makroekonomické prostředí a obsahuje návrhy implementace marketingové strategie ve společnosti.

The Master´s thesis deals with proposal and creation marketing strategy. Thesis describes state of the Eurovia CS, a.s., analyzes microeconomics and macroeconomics surrounding and contains proposals of implementation marketing strategy in the company.
Marketing Strategy for Company Eurovia
Keywords: Marketing; Marketingová strategie; Marketingový mix; SWOT analýza; PEST analýza; Analýza 7S; Marketing; Marketing strategy; Marketing mix; SWOT analysis; PEST analysis; 7S analysis